The determination of antimicrobial susceptibility by MIC and epidemiological cut‐off values and the detection of resistance genes in Aeromonas species isolated from cultured fish. (1st November 2020) - Duman, M.; Saticioglu, I.B.; Altun, S.
Abstract: The present study was aimed at determining antimicrobial susceptibility by a CLSI standard microdilution testing protocol and detecting the resistance genes of motile Aeromonas species isolated from cultured fish. The importance of the minimum inhibitory concentrations was assessed based on statistically determined epidemiological cut‐off values calculated by normalized resistance analysis. Unfortunately, CLSI epidemiological cut‐off values are available only for Aeromonas salmonicida, and there is no further detailed data on Aeromonas isolated from aquatic animals. The antimicrobial susceptibilities of pre‐identified motile Aeromonas species to florfenicol, tetracycline and sulfamethoxazole were determined by calculating epidemiological cut‐off values with fully automated and freely available Excel spreadsheets, applying the normalized resistance interpretation (NRI) method. Furthermore, the presence of the antimicrobial resistance genes flo R, tet A, tet B, tet C, tet D, tet E, tet H, sul I, sul II and sul III was detected by PCR analysis and confirmed by sequence analysis. The presence of up to six different genes (multiple antimicrobial resistance) was determined in the Aeromonas isolates. Significance and Impact of the Study: Significance and Impact of the Study: In this study, we investigated phenotypic and genotypic antimicrobial resistance characteristics by a novel method based on epidemiological cut‐off values. This is the second comprehensive study on the antimicrobial susceptibility characteristics of Aeromonas species using NRI and epidemiological cut‐off values. The present research is related to our previous researches focussed on the identification of motile Aeromonads, their prevalence in relation to different fish lengths, seasons and regions, and covered the investigation of Lactococcus garvieae, Yersinia ruckeri, Flavobacterium spp., Enterobacter spp. and Citrobacter spp.